171k views
4 votes
Solve this quadratic formula -3x^2 +16 +12

User Javicobos
by
5.4k points

2 Answers

3 votes

1.). Solve this quadratic formula:

-3x^2 + 16 + 12 =====> Solution -3x^2 + 28

Let's simplify step-by-step.

−3x^2 + 16 + 12

Combine Like Terms:

= −3x^2 + 16 + 12

= (−3x^2) + (16 + 12)

= −3x^2 + 28

Answer:

= −3x^2 + 28

Answer =======> -3x^2 + 28











2). Solve the Quadratic Formula:

-3x^2 + 16x + 12 =====> - ( x - 6 ) ( 3x + 2 )

Steps:

-3x^2 + 16x + 12

Factor out Common Term -1:

- (3x^2 - 16x - 12 )

Factor:

3x^2 - 16x - 12: ( x - 6 ) ( 3x + 2 )

x^1 =======> -2/3

x^2 =======> 6

Answer =========> - (x - 6 ) ( 3x + 2 )





Hope that helps!!!! : )



User TrapII
by
5.6k points
5 votes

Solve for x over the real numbers:

-3 x^2 + 16 x + 12 = 0

The left hand side factors into a product with three terms:

-(x - 6) (3 x + 2) = 0

Multiply both sides by -1:

(x - 6) (3 x + 2) = 0

Split into two equations:

x - 6 = 0 or 3 x + 2 = 0

Add 6 to both sides:

x = 6 or 3 x + 2 = 0

Subtract 2 from both sides:

x = 6 or 3 x = -2

Divide both sides by 3:

Answer: | x = 6 or x = -2/3

User Hemesh Singh
by
6.6k points